2013
DOI: 10.1145/2503823
|View full text |Cite
|
Sign up to set email alerts
|

Health Mashups

Abstract: People now have access to many sources of data about their health and wellbeing. Yet, most people cannot wade through all of this data to answer basic questions about their long-term wellbeing: Do I gain weight when I have busy days? Do I walk more when I work in the city? Do I sleep better on nights after I work out?We built the Health Mashups system to identify connections that are significant over time between weight, sleep, step count, calendar data, location, weather, pain, food intake, and mood. These si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(33 citation statements)
references
References 30 publications
1
32
0
Order By: Relevance
“…Increased self-consciousness helps to focus on certain behaviour and can improve well-being [25]. Earlier studies about migraine patients' willingness to wear sensors to detect migraine pre-symptoms and their pre-symptoms revealed that 88.8% of the respondents wanted a device to detect an upcoming migraine attack.…”
Section: Related Workmentioning
confidence: 99%
“…Increased self-consciousness helps to focus on certain behaviour and can improve well-being [25]. Earlier studies about migraine patients' willingness to wear sensors to detect migraine pre-symptoms and their pre-symptoms revealed that 88.8% of the respondents wanted a device to detect an upcoming migraine attack.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, the data made available to the user from PI tools are usually visualizations of the monitored phenomena, with, at most, simple correlations among user's activities which are displayed using natural language [2]. EUM, and especially its cognitive part, would provide information one step ahead: it will allow to correlate not only the activities among themselves and with the user's attitudes, but also with the user's cognitive states and skills involved in those activities.…”
Section: Enriching the Qs With The Eummentioning
confidence: 99%
“…Epstein et al visualized subsets of collected location and physical activity data using a variety of presentations [16]. Bentley et al developed a system that aggregates multiple aspects of personal well-being data and provides people with insights based on complex relations using natural language [17]. They showed that users were able to understand complex relationships and change their behavior to improve their well-being.…”
Section: Introductionmentioning
confidence: 99%